Uncovering key determinants of well-being among older Canadian retirees in New Brunswick: Protocol for a mixed-methods study - Yasin M. Yasin; Areej Al-Hamad; Kateryna Metersky; Emily Richard (PLoS ONE, 2025)
Aims To uncover the key determinants of physical, mental, social, financial, and spiritual well-being among older Canadian retirees living in New Brunswick and explore how individual, community, organizational, and societal factors interact to shape healthier, more fulfilling aging. Design Explanatory sequential mixed-methods study guided by the Socio-Ecological Model. Methods A cross-sectional survey will be conducted with 600 retirees aged 65 and older using the WISE Scale, a multidimensional measure of well-being. Surveys will be offered online and in person with accessibility supports. Data will be analyzed in SPSS using descriptive statistics and multiple regression. A purposive subsample of 15–25 participants will be invited for semi-structured interviews to enrich understanding of survey findings. Interviews will be thematically analyzed in NVivo, following the four pillars of trustworthiness. Triangulation will integrate quantitative and qualitative findings. Discussion The study will generate detailed insights into how multiple layers of influence affect older adults’ well-being in retirement, addressing critical gaps in research, policy, and practice. Findings will inform tailored community programs, effective strategies for healthcare providers, equitable policies, and age-friendly supports that promote holistic well-being for older retirees in New Brunswick, particularly among English-speaking populations. By identifying specific factors that enhance or hinder well-being, this research will support more responsive and inclusive strategies for healthy aging.